TRANSFORMATION OF CURRICULUM MANAGEMENT BASED ON KE-NU-AN VALUES IN IMPROVING THE QUALITY OF VOCATIONAL EDUCATION AT VOCATIONAL HIGH SCHOOLS - Muhlil Musolin; Devi Pramitha; Sugiarti (Program Studi Manajemen Pendidikan Islam, 2026)
This study is grounded in the growing demand for vocational education that not only produces technically competent graduates but also cultivates moderate religious character and professional work ethics. It aims to analyze the transformation of curriculum management based on Nahdlatul Ulama (NU) values in improving the quality of vocational education at SMK Ma’arif NU 02 Kemiri Purworejo. The study employed a qualitative approach with a phenomenological research design. The research participants included the principal, the vice principal for curriculum affairs, and teaching staff. Data were collected through in-depth interviews, observations, and document analysis. Data trustworthiness was ensured through source and technique triangulation, member checking with participants, and prolonged engagement in observation to enhance the credibility of the findings. Data analysis was conducted using interactive techniques involving data reduction, data display, and conclusion drawing. The findings reveal that the transformation of curriculum management was implemented through four main stages: (1) curriculum planning based on the integration of vocational competencies and NU values; (2) curriculum organization through the distribution of professional responsibilities, management of learning schedules, and provision of supporting facilities; (3) curriculum implementation at both school and classroom levels through the development of a religious culture and practice-based learning; and (4) curriculum evaluation through formative and summative assessments as part of a continuous quality assurance system. The study confirms that the integration of NU values throughout the entire curriculum management cycle serves as a strategic factor in enhancing the quality of vocational education. The novelty of this research lies in its curriculum management transformation model based on the values of a religious organization, which systematically integrates occupational competencies, religious moderation, and a religious school culture